Pengembangan E-modul berbasis Flipbook pada Mata Pelajaran Dasar-Dasar Desain Komunikasi Visual Kelas X DKV SMKN 2 Bone - Aidil Fikran; Suhardiman; Jusman (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This research aims to (1) To determine the development of a Flipbook-Based E-module in the Basics of Visual Communication Design Subject for Class X DKV UPT SMKN 2 Bone. (2.) To determine the validity of developing a flipbook-based e-module in the Basics of Visual Communication Design subject for Class X DKV UPT SMKN 2 Bone. (3) To find out the practicality of developing a flipbook-based e-module in the Basics of Visual Communication Design subject for Class X DKV UPT SMKN 2 Bone. The ADDIE (analysis, development, implementation and evaluation) model is used in this research and development (R&D). Qualitative and quantitative data were used in this research. Qualitative data consists of students' opinions regarding the products produced as well as validator comments and suggestions. Meanwhile, measurable data comes from student response questionnaires and media, material and language validation. This research was carried out at UPT SMKN 2 Bone. Interviews, observations, student response questionnaires, and expert validation questionnaires were used to collect research data. After that, the data is checked to ensure the level of validity and practicality of the product. The results of research and development include (1) teaching materials in the form of Flipbook-based E-modules in the Basics of Visual Communication Design subject for Class 53 in the very valid category, material validation results with an average score of 3.69 in the very valid category, and language validation results with an average score of 3.20 in the valid category with an overall validation average of 3.47 in the valid category , (3) the results of the practicality of the electronic module from student response questionnaires through large-scale trials with an average score of 83% in the very practical category. The conclusion of this research is that the development of a Flipbook-Based E-module for the Basics of Visual Communication Design Subject for Class X DKV UPT SMKN 2 Bone is valid and very practical.